(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research study has set 3 research objectives: 1) to survey the knowledge and review the problems related to local finance and budget management; 2) to study public fiscal and budget problems affecting the public services organization in Phitsanulok Local Government Organizations and 3) to study ways to solve fiscal and budget problems to lead to the provision of public services of the local government organization in Phitsanulok Province to be worthwhile, efficient and effective as well as bringing about satisfaction with the people who receive the most services. The research methodology was a combination of methods based on document synthesis. The sample group consisted of 20 people. The instruments used were questionnaires and in-depth interviews. The statistics used for data analysis were frequency, average, standard deviation, and content analysis. The study revealed that: Local fiscal management issues are divided into 1) local fiscal management issues related to “government” 2) problems of relations and conflicts between local government organizations and central agencies 3) local fiscal management issues related to the "local government organization" and 4) problems of financial management related to "people". As for the public finance and budget problems are concerned, the three areas affecting the provision of public services, overall, were at medium level, equal to (Mean = 3.21, SD = 0.72). The most problematic side was income acquisition, equal to (Mean= 3.48, SD = 0.72), followed by spending (Mean = 3.12, SD = 0.68) and public debt was (Mean = 3.04, SD = 0.77). For solutions to fiscal and budget problems, there should be a promotion of development in the administration of finance and budgets of the local administrative organization to lead to the provision of public services to be worthwhile, efficient, and effective as well as binging about the satisfaction of the people who receive the service the highest by linking with the government. Since the government is the policymaker and the mission is transferred to the local government organization as the operator, based on the transferred policy. the development and administration of the local government’s finance and budget must be taken seriously. Moreover, the government should expand the tax base and set local sources of income, such as tourism taxes may be collected from accommodation businesses. Travel companies, etc. In addition, the government should provide tax incentives to business establishments in the tourism industry that provide funding to preserve local culture as well as the introduction of tourism tax to fund for conservation and sustainable tourism development so that the local area can have more sources of income in the store, including other sources of income or new sources of income that happened locally.